Spatial and temporal variation in microcystin occurrence in wadeable streams in the southeastern United States. (6th June 2016) - Loftin, Keith A.; Clark, Jimmy M.; Journey, Celeste A.; Kolpin, Dana W.; Van Metre, Peter C.; Carlisle, Daren; Bradley, Paul M.
Abstract: Despite historical observations of potential microcystin‐producing cyanobacteria (including Leptolyngbya, Phormidium, Pseudoanabaena, and Anabaena species) in 74% of headwater streams in Alabama, Georgia, South Carolina, and North Carolina (USA) from 1993 to 2011, fluvial cyanotoxin occurrence has not been systematically assessed in the southeastern United States. To begin to address this data gap, a spatial reconnaissance of fluvial microcystin concentrations was conducted in 75 wadeable streams in the Piedmont region (southeastern USA) during June 2014. Microcystins were detected using enzyme‐linked immunosorbent assay (limit = 0.10 µg/L) in 39% of the streams with mean, median, and maximum detected concentrations of 0.29 µg/L, 0.11 µg/L, and 3.2 µg/L, respectively. Significant (α = 0.05) correlations were observed between June 2014 microcystin concentrations and stream flow, total nitrogen to total phosphorus ratio, and water temperature; but each of these factors explained 38% or less of the variability in fluvial microcystins across the region. Temporal microcystin variability was assessed monthly through October 2014 in 5 of the streams where microcystins were observed in June and in 1 reference location; microcystins were repeatedly detected in all but the reference stream. Although microcystin concentrations in the present study did not exceed World Health Organization recreational guidance thresholds, their widespread occurrence demonstrates the need for further investigation of possible in‐stream environmental health effects as well as potential impacts on downstream lakes and reservoirs. Environ Toxicol Chem 2016;35:2281–2287. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.